(3efGXQI GdMQejf hefGVdI GdeMdjfs - (3Ydj Hf jhSa Hf GdMSf GdRQfOj GdCfUGQj GdMfaj, CHhGdMSf fhQ GdOjf,J (B772 (3g` s
(3ChdgG (B:s
(3bGd YaG Gddg Yfg(B: (3ef WQja GdeMGVQI hXQja GdePGcQI s
(3BNQgG (B:s
(3hfgVJG bGadJjf XGaQJjf HSDdgeG hGdSdGe JeJ GdQSGdI HYhf Gddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B265s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B105 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs